Conversion Narratives as Mirrors of Religious Encounters: Perspectives from a German Missionary in South India (1924–1926) = Les récits de conversion comme miroirs d’interactions religieuses: Perspectives d’un missionnaire allemand en Inde du Sud (1924–26) - Bornet, Philippe (Social sciences and missions, 2024)
This article focuses on the narratives that emerged from two conversion episodes in Kerala in the 1920s involving the German missionary Paul Sengle (1870–1932): the conversion of a young Hindu woman named Kalyani and attempts to convert members of the Ezhava caste amid competition from Hindus, Muslims, and Buddhists. While mainly drawing on materials produced by the Basel Mission or by missionaries in the field like Sengle, this article also gives space to the perspectives of the newly converted person and of the rival religious communities. It suggests studying conversion experiences as shaped by situations of interaction, by connecting sources that represent the divergent perspectives of all the parties involved in such cases. This approach helps to examine the different sides of a conversion experience at both macro and micro levels and offers insights into the broader processes of religious encounters in the early twentieth century global history of religions.